Process modelling and techno economic analysis for optimal design of integrated electrocoagulation-membrane system for dye removal in wastewater - Saad, M.S. (Elsevier Ltd, 2022)
Textile industry, one of the largest exporting industries in Malaysia, generates azo dyes wastewater which cannot be easily decomposed biologically due to its high stability and xenobiotic nature. Conventional electrocoagulation (EC) system requires high energy consumption, resulting in higher operating cost while membrane system suffers from fouling. To eliminate these drawbacks, an integrated electrocoagulation â membrane (ECM) system has been proposed as one of the emerging methods for treating dye wastewater. However, feasibility analysis of the proposed system is yet to be conducted. This study proposes a statistical technique to evaluate the techno-economic feasibility of the system via John's Macintosh Project (JMP) software. From JMP, an equation represents the whole model had been obtained for each of the system, EC standalone and ECM system. The models have been validated experimentally it is proven all the models can reach dye removal efficiency of 96. Overall, the total cost for ECM system (1 V and 1.0 g of NaCl) was 40.44 cheaper than the conventional dye treatment method with total cost of 1.079 million MYR. EC standalone system at 1 V and 1.0 g however were found to be more economically feasible with 0.325 million MYR or 82.07 cheaper compared to conventional photocatalytic method. EC standalone system was also more economical than ECM system due to lower capital cost expended for installation of membrane tank and additional membrane purchase. Â© 2022